The Correlation Between pH Values and Acidity Degrees of Dadih from Gayo to Total Bacteria Colonies with Different Storage Time and Temperature - Rastina, Rastina; Ferasyi, Teuku Reza; Azhari, Azhari; Rasmaidar, Rasmaidar; Hasan, Denny Irmawati; Helmi, T Zahrial; Sitepu, Dinda Meilinda Br (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
Dadih is a traditional food product that is produced by storing buffalo milk in bamboo tubes and left for 2-3 days. During the process of making Dadih, milk ferments into Dadih in a bamboo tube. The aim of this research is to determine the quality of buffalo Dadih from pH values, acidity degrees, and total bacterial colonies with different storage durations and temperatures. This research used 12 bamboo tubes with two treatments and three repetitions. This research used a laboratory experimental method with a 2x3 factorial pattern. This research showed that the highest room and refrigerator pH values were found in the first week, with an average of 7.13 0.15 and 7.9 0.1. The highest acidity degree values from room temperature and refrigerator were in the third week, with 359.47 16.95 and 254.03 6.34. Another finding was that the highest total bacterial colonies at room temperature and in the refrigerator were in the third week, with 3.33 0.89 and 2.8 0.76. It can be concluded that the buffalo Dadih from Gayo has a pH value and a total value of bacterial colonies that meet SNI standards. Meanwhile, the total titrated acid in Dadih does not yet have an SNI standard.